2021
DOI: 10.1515/reveh-2020-0136
|View full text |Cite
|
Sign up to set email alerts
|

Air pollutants and impairments of male reproductive health-an overview

Abstract: Excessive air pollution, both ambient and indoor are might be detrimental to human wellbeing and are related to morbidity and mortality, it may also affect the reproductive function and its outcome. It is a recognized fact that air pollution contains several toxicants, gases, particulate matter, toxic metals etc. Some of them might affect reproductive and developmental process and a few are persistent. The information accessible on air pollution to human male reproduction is stated to affect semen quality by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…These health harms include exacerbation of chronic respiratory and cardiovascular conditions; increased occurrence of acute cardiovascular events and metabolic, dermatologic, and mental health disorders; increased susceptibility to respiratory infections such as influenza and SARS-CoV-2; immune dysfunction; adverse pregnancy outcomes; sperm damage; infant developmental disorders; and dementia. 15,[32][33][34][35][36][37][38][39][40][41][42][43][44] Increases in asthma attacks and asthma hospitalization are associated with wildfires. A study found that use of prescribed burns, which can decrease size and severity of wildfires, may be beneficial for immune health.…”
Section: Increasing Intensity and Frequency Of Wildfiresmentioning
confidence: 99%
“…These health harms include exacerbation of chronic respiratory and cardiovascular conditions; increased occurrence of acute cardiovascular events and metabolic, dermatologic, and mental health disorders; increased susceptibility to respiratory infections such as influenza and SARS-CoV-2; immune dysfunction; adverse pregnancy outcomes; sperm damage; infant developmental disorders; and dementia. 15,[32][33][34][35][36][37][38][39][40][41][42][43][44] Increases in asthma attacks and asthma hospitalization are associated with wildfires. A study found that use of prescribed burns, which can decrease size and severity of wildfires, may be beneficial for immune health.…”
Section: Increasing Intensity and Frequency Of Wildfiresmentioning
confidence: 99%
“…Information on sleep status and potential confounding factors obtained from questionnaires might be subject to recall bias. Third, this study failed to completely exclude confounding bias because some covariates were unmeasured, such as genetic factors ( Ni et al, 1997 ; Ley et al, 2018 ), air pollutants ( Kumar et al, 2021 ; Sun et al, 2020 ), and water and soil pollution ( Di Nisio and Foresta, 2019 ), which might influence the aforementioned associations. Further research is needed to rule out the possibility of residual confounders and better elucidate the association between sleep status and asthenozoospermia risk.…”
Section: Discussionmentioning
confidence: 98%
“…Some of them could affect the reproductive process and sperm quality by decreasing one or more sperm quality parameters i.e., sperm morphology, concentration, motility, sperm DNA damage, up to testicular cancer. The impact could be related to the concentration of pollutants and the duration of exposure [206]. PAHs, formed by pyrogenic, petrogenic and biogenic (biological) processes, are defined as persistent organic pollutants (POPs); two of them, 7, 12-dimethylbenzo[a]anthracene (DMBA) and benzo[a]pyrene (B[a]P), are among the most widely studied carcinogenic PAHs for their negative impact on the environment, human and animal health.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%